TET2 is a Master Regulator of Smooth Muscle Cell Plasticity - Liu, Renjing (2013)
BACKGROUND: Smooth muscle cells (SMC) are remarkably plastic. Their reversible differentiation is required for growth and wound healing, but also contributes to pathologies including atherosclerosis and restenosis. While key regulators of the SMC phenotype including myocardin (MYOCD) and KLF4 have been identified, a unifying epigenetic mechanism that confers reversible SMC differentiation has not been reported. METHODS AND RESULTS: Using human SMC, human arterial tissue, and mouse models, we report that SMC plasticity is governed by the DNA modifying enzyme ten-eleven translocation-2 (TET2). TET2 and its 5-hydroxymethylcytosine (5-hmC) product are enriched in contractile SMC but reduced in dedifferentiated SMC. TET2 knockdown inhibits expression of key pro-contractile genes including MYOCD and SRF with concomitant transcriptional upregulation of KLF4. TET2 knockdown prevents rapamycin-induced SMC differentiation, while TET2 overexpression is sufficient to induce a contractile phenotype. TET2 overexpression also induces SMC gene expression in fibroblasts. Chromatin immunoprecipitation demonstrates that TET2 coordinately regulates phenotypic modulation through opposing effects on chromatin accessibility at the promoters of pro-contractile versus dedifferentiation-associated genes. Notably, we find that TET2 binds, and 5-hmC is enriched, in CArG-rich regions of active SMC contractile promoters (MYOCD, SRF, and MYH11). Loss of TET2 and 5-hmC positively correlates with the degree of injury in murine models of vascular injury and human atherosclerotic disease. Importantly, localized TET2 knockdown exacerbates injury response while local TET2 overexpression restores the 5-hmC epigenetic landscape, contractile gene expression, and greatly attenuates intimal hyperplasia in vivo. CONCLUSIONS: We identify TET2 as a novel and necessary master epigenetic regulator of SMC differentiation.